1H NMR Study of "Host–Guest" Interactions of Micellar Assemblies from Amphiphilic Invertible Polymers and Peptides. Issue 21 (22nd September 2017) - Kohut, Ananiy; Zholobko, Oksana; Hevus, Ivan; Voronov, Andriy
Abstract: "Host–guest" interactions between self‐assembled micellar nanostructures from amphiphilic invertible polymers (AIPs) and two peptides, swine‐origin Influenza A surface protein Hemagglutinin and research antibody peptide V5, are investigated by changing the polymer concentration and polymer/peptide ratio in the aqueous solution. Formation of mixed micellar assemblies from AIP and each peptide is revealed using detailed 1 H NMR spectroscopic study. Peptide molecule localization in the micellar assemblies depends on the specific interactions between amino acid functional groups of the peptide and polymer fragments. The resulting mixed micellar structures can be considered as a promising material toward delivery and stimuli‐responsive sustained release of peptides. Abstract : A detailed 1 H NMR spectroscopic study reveals "host–guest" interactions between self‐assembled micellar nanostructures from amphiphilic invertible polymers and peptides. Mixed micellar assemblies with incorporated peptide molecules are formed. The inner part of the assemblies consists of the hydrophobic moieties of both the polymer and the peptide, whereas the hydrophilic fragments of the polymer and peptide comprise the exterior.